Stabilization studies 4-aminoantipyrine by quantum calculations (Journal of the College of Basic Education, 2022)
In this study, Stabilization studies has been studied by using of AM1 and MNDO. The calculations methods used with complete geometry optimization have been performed on 4-aminoantipyrine. Thermodynamically with theoretical calculations. Geometrical parameters, heats of formation, electron densities and orbital energies (HOMO-LUMO) are also studied.